Characterization of mid-intestinal microbiota of farmed Chinook salmon using 16S rRNA gene metabarcoding - Ciric, Milica; Waite, David; Draper, Jenny; Jones, John Brian (Archives of Biological Sciences, 2019)
Paper description: With worldwide growth of aquaculture, the characterization of microbiota of high-value aquaculture species is of special interest. This paper reports a novel workflow for high-throughput surveys of bacterial intestinal microbiota of aquacultured fish using metabarcode profiling of the V3-V4 hypervariable region of the bacterial 16S rRNA gene. The workflow was used to produce the first 16S rRNA gene metabarcoding survey of the mid-intestinal microbiota of farmed Chinook salmon. The presented workflow could be applied to other aquacultured fish species to capture variation or dysbiosis occurring as a result of changes in feed, health or environmental conditions. Abstract: With the growing importance of aquaculture worldwide, characterization of the microbiota of high-value aquaculture species and identification of their shifts induced by changes in fish physiology or nutrition is of special interest. Here we report the first 16S rRNA gene metabarcoding survey of the mid-intestinal bacteria of Chinook salmon (Oncorhynchus tshawytscha), an economically important aquacultured species. The microbiota of 30 farmed Chinook salmon from a single cohort was surveyed using metabarcode profiling of the V3-V4 hypervariable region of the bacterial 16S rRNA gene. Seawater, feed and mid-intestinal samples and controls were sequenced in quadruplicate to assess both biological and technical variation in the microbial profiles. Over 1000 operational taxonomic units were identified within the cohort, providing a first glimpse into the mid-intestinal microbiota of farmed Chinook salmon. The taxonomic distribution of the salmon microbiota was reasonably stable, with around two thirds of individuals dominated by members of the family Vibrionaceae. We anticipate that the workflow presented in this paper could be applied in other aquacultured fish species to capture variation or dysbiosis occurring as a result of changes in feed, health or environmental conditions. https://doi.org/10.2298/ABS190402040C Received: April 2, 2019; Revised: June 15, 2019; Accepted: July 3, 2019; Published online: July 17, 2019 How to cite this article: Ciric M, Waite D, Draper J, Jones JB. Characterization of mid-intestinal microbiota of farmed Chinook salmon using 16S rRNA gene metabarcoding. Arch Biol Sci. 2019;71(4):577-87.